EFEKTIVITAS BAHAN INSTRUKSIONAL PENDIDIKAN AGAMA ISLAM - Agus Suradika; Widia Winata; Dirgantara Wicaksono; Rifqiyati Rifqiyati (Universitas Muhammadiyah Jakarta, 2020)
The aim of this research is to determine the effect of instructional material on the echievement in Islamic Education. The experiment was conducted at the Faculty of Social and Political Sciences, the University of Muhammadiyah Jakarta, during the second semester of the academic year 2018/2019, using “The two-groups posttest-only randomized experiment”. A sample of 60 students was ramdomly choosen from the available students, i.e. 30 students for individualized instructional material, and 30 students others for the PBS one. The result of hyphotheses testing showed that Individualized instructional material ( = 81,37) resulted in a better achievement than the PBS one ( = 77,39)